2015
DOI: 10.1037/h0100352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saccadic eye movements on postural control in older adults.

Abstract: Saccadic eye movements have been shown to affect posture by decreasing the magnitude of body sway in young adults. However, there is no evidence of how the search for visual information that occurs during eye movements affects postural control in older adults. The purpose of the present study was to determine the influence of saccadic eye movements on postural control in older adults while they stood on 2 different bases of support. Twelve older adults stood upright in 70-s trials under 2 stance conditions (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
5
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
4
34
5
9
Order By: Relevance
“…Stoffregen et al (2006) found that head and trunk sway changes while performing saccades and visual fixation with the eyes closed and open. In particular, body sway is more reduced during SEM than gaze fixation, and the amplitude of postural sway is reduced in both young adults and the elderly during SEM (Aguiar et al 2015). These findings suggest that elderly individuals depend on vision to control postural balance.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Stoffregen et al (2006) found that head and trunk sway changes while performing saccades and visual fixation with the eyes closed and open. In particular, body sway is more reduced during SEM than gaze fixation, and the amplitude of postural sway is reduced in both young adults and the elderly during SEM (Aguiar et al 2015). These findings suggest that elderly individuals depend on vision to control postural balance.…”
Section: Introductionmentioning
confidence: 57%
“…In total, 104 elderly participants who could walk unaided were screened. In previous studies (Aguiar et al 2015;Rodrigues et al 2015), the subjects were young adults and elderly individuals, but the sex was not disclosed. More than 80% of the subjects who wished to participate in this study were women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the Gibsonian notion of visual system ("eyes-in-the-head-on-the-bodyresting-on-the-ground"; Gibson, 1979, p. 205) favors the simultaneous consideration of gaze and postural data during motor actions. Continuous and predictable saccadic and smooth pursuit eye movements improve postural stabilization during quiet stance (Aguiar et al, 2015;Rodrigues et al, 2013;Rodrigues et al, 2015); in more dynamical contexts, increased postural stability due to motor learning has been reported in a variety of motor skills, such as rifle shooting (Era, Konttinen, Mehto, Saarela, & Lyytinen, 1996) and manual rhythmic movements (Amado, Palmer, Hamill, & van Emmerik, 2016). Interestingly, expertise of ball cascade jugglers seems associated with parsimonious oculomotor and attention pattern ("gaze-through" strategy) with fixations at the scene's central location, weaker frequency locking between point-of-gaze and ball movements, reduced dependency to visually tracking ball motion, and improved anterior-posterior body sway stabilization (Dessing, Rey, & Beek, 2012;Huys & Beek, 2002;Huys, Daffertshofer, & Beek, 2004;Rodrigues et al, 2016), which is in line with experts' higher capability of decoupling postural control and arm movements (Amado et al, 2016).…”
Section: Posture Supporting Qementioning
confidence: 99%